Measurement of Activity Concentration of 40K, 226Ra and 232Th in Commercial Wall Paints Used in Nigeria and Inherent Radiological Hazards - Echeweozo, E. O.; Onwunyiriuwa, G. M.; Nwigwe, P. A. (Journal of Sustainability and Environmental Management, 2022)
Ionizing radiations from building materials portend serious health risk to atoms and molecules of body cells by damaging tissues and altering the DNA in genes. In this study, the measurement of radioactivity concentration of 40K, 226Ra and 232Th to determine inherent radiological hazards in major brands of commercial wall paints used in Nigeria was carried out. Twenty paint samples were selected based on the popularity and quantity of sales of these paints’ brands as obtained from oral interview with these paints’ marketers. A NaI (Tl) detector (76×76 mm) was employed in the measurements. High mean levels of the radioactivity of 40K, 226Ra and 232Th were observed in emulsion paints 174.73, 58.18 and 56.98 Bq/kg while oil paints gave lower values of 119.66, 44.66 and 37.86 Bq/kg for 40K, 226Ra and 232Th respectively. From results obtained, most of the emulsion and oil paints available in Nigeria present low level of radioactivity concentration which does not pose significant radiological risk to user population. However, average excess lifetime cancer risk of these paints gave a value higher than the recommended limit. Based on this, regulation, quality control and constant monitoring of raw materials used for paint production in Nigeria is highly advised.